The Determination of sobriety BY time Discounting (based on sociological study results) - Klochko, Marianna (Ukrainian Sociological Journal, 2015)
This paper reports the results of a simple questionnaire given to 141 active members of Cocaine Anonymous at over a half-dozen distinct meeting groups for the purpose of gauging differences in individual time discounts.  Starting with the idea that addicts are notably `impatient’ with respect to rewards, we offer evidence in support of the argument that, among the impacts of a 12-step recovery program such as CA on individual motives, discounts vary endogenously across (and by implication, within) recovering addicts as a function of the duration of their sobriety. Although our analysis is also consistent with the hypothesis that addicts with longer time horizons are more likely to remain in a drug rehabilitation program, our data is also consistent with the hypothesis that regular participation impacts `impatience’ and has its  greatest effect with regular (at least once weekly) attendance over a period of five or more years. This study, then, can be viewed as a call for additional research in which the effects of self-selection and endogenous time preference change are sorted out.